Period of public commentary begins on the revised proposal of species-group level names, and on the proposal of genus-group level names of the Candidate Part of List of Available Names (LAN) in the phylum Rotifera - Segers, Hendrik; Smet, Willem H. De; Fontaneto, Diego; Hinz, Claus; Hussey, Charles; Michaloudi, Evangelia; Wallace, Robert L.; Jersabek, Christian D. (Zootaxa, 2016)
Following ICZN (1999) Article 79 Chapter 17 http://www.nhm.ac.uk/hosted-sites/iczn/code/), we, with the full support of the international community of rotifer researchers as expressed during subsequent international Rotifera symposia, developed a Candidate Part of the List of Available Names for species and genera of Rotifera from the start of zoological nomenclature to the year 2000.